INTERPRETASI GEOFISIKA BIDANG GELINCIR PALEO-ROCKSLIDE PARANGTRITIS - Akroma Hidayatika; Suharno Suharno; Rahmi Mulyasari; Hesti Hesti; Bella Restu Juliarka (Jurnal Geofisika Eksplorasi, 2020)
Parangtritis has a rock fall hazard area with a medium to high level of risk. In Parangtritis, there was a large scale paleo-rockslide that involved more than 800 million m3 of rock mass with an area of 1500 m x 2700 m. This is a significant factor in changing the landscape. This research uses 9 Audio-MagnetoTelluric (AMT) primary data points. Using the distance between points 750 m within a 2 km x 2 km study area. The location focused on the western side of the paleo-landslide area in Parangtritis Village. Processing AMT data using the help of MT-INV and RockWorks software. The result of one-dimensional inversion consists of 3 layers. Indicates a low resistivity value (0-10 Ωm) interpreted as beach deposition and sand dune, medium resistivity (50 - 160 Ωm) for Wonosari limestone and high resistivity ( 170 Ωm) for Nglanggran andesite breccias. The average thickness of the first layer is 44 m and the second layer reaches 175 m. Based on the resistivity structure of the AMT data, the interpretation of the boundary contact between the Wonosari limestone and the Nglanggran andesite breccia can act as a slip field in a depth of about 250 m This field is a passive fault field controlled by the Girijati fault in the east of the study area.